Islamic Counseling as an Intervention for Enhancing Social Empathy and Caring Behavior among Secondary School Students - Fitriani Fitriani; Nurhanifah Nurhanifah (Al-Qalam Institue, 2026)
This study examines the implementation of an Islamic counseling approach in fostering students’ social empathy and concern for others at senior high school. A qualitative descriptive design was employed to explore the counseling process, the forms of Islamic counseling implemented, and the perceived contribution of Islamic values to students’ social development. Data were collected through observations, in-depth interviews with guidance and counseling teachers, and analysis of relevant school documents. The data were analyzed using the Miles, Huberman, and Saldaña framework through data condensation, data display, and conclusion drawing and verification. The findings indicate that students’ social empathy and concern were generally adequate but remained uneven, with insensitive behaviors such as teasing peers based on socioeconomic differences still occurring in everyday interactions. Islamic counseling was implemented through individual counseling, group counseling, personal and relational approaches, and recurring Islamic habituation activities, including Qur’an reading before the Dhuhr prayer. The counseling process emphasized active listening, contextual Islamic guidance, self-reflection, and the internalization of values such as respect, ukhuwah (brotherhood), ta'awun (mutual assistance), and rahmah (compassion). The findings suggest that these practices contributed to greater awareness of the emotional consequences of interpersonal behavior and encouraged more caring and respectful interactions among students. The study highlights the potential of Islamic counseling as a holistic approach to integrating psychological, spiritual, moral, and social development in secondary education.